Chemical and biological indicators for evaluation of Arctic soil degradation and its potential to remediation - Smirnova, Tatiana S.; Mazlova, Elena A.; Kulikova, Olga A.; Ostrovkin, Ilya M.; Gonopolsky, Adam M.; Cheloznova, Kristina V. (Journal of Environmental Engineering and Landscape Management, 2021)
In recent years, significant efforts have been made to accelerate the economic development of the Arctic zone, leading to intense environmental pollution of this region, accompanied by the significant impact of accumulated environmental damage in the region. The solution to these problems is difficult due to the remoteness of these areas and severe climatic conditions. Therefore, it is important to evaluate the potential for restoration of arctic soils. For this purpose, various indicators are used, including biological ones.In the analyzed arctic soil samples, high concentrations of petroleum hydrocarbons (up to 47,000 mg/kg) and chloride-ions (0.10–0.14 wt %) were established. Microbioassay demonstrated a presence of hydrocarbon-oxidizing microorganisms: Penicillium, Azotobacter chroococcum, Bacillus subtilis, Pseudomonas oleovorans.A low enzymatic activity and specific Arctic climate point out a low self-restoration ability of the soil, demonstrated the need for its remediation.The microbioassay with microbial strains identification and soil remediation methods suitable for the Arctic zone were recommended.